Waste recycling: utilization of coffee grounds and kitchen waste in vermicomposting - Adi, A.J.; Noor, Z.M. (2009)
Vermicomposting using Lumbricus rubellus for 49 days was conducted after 21 days of pre-composting. Three different combination of treatments were prepared with eight replicates for each treatment namely cow dung: kitchen waste in 30:70 ratio (T(1)), cow dung: coffee grounds in 30:70 ratio (T(2)), and cow dung: kitchen waste: coffee grounds in 30:35:35 ratio (T(3)). The multiplication of earthworms in terms of numbers and weight were measured at the end of vermicomposting. Consequently, only T(2) showed significant increase (from it initial stage) compared to other treatments. The presence of coffee grounds in T(2) and T(3) showed higher percentage of nutrient elements in vermicompost produced. The data reveal that coffee grounds can be decomposed through vermicomposting and help to enhance the quality of vermicompost produced rather than sole use of kitchen waste in vermicomposting.